"When are you gonna commit?" Exploring the experiences of youth athletes and their parents prior to a sporting transition. Issue 4 (4th July 2022) - Dunn, Rachel; Tamminen, Katherine A.
ABSTRACT: The aim of this research was to explore the experiences of youth athletes and their parents in the lead up to a sporting transition into the development years of competitive sport. Parents ( n  = 6) and children ( n  = 5) were interviewed from sports teams in the Greater Toronto Area. Case study methodology and phenomenological analysis were used to explore each athlete and parents' individual experience and, where appropriate, cross-case comparisons were made. Results indicate that athletes experienced psychosocial challenges prior to their transition, such as anxiety about competitive soccer. Parents were the primary support network and experienced their own stressors such as shielding their child from organisational politics in youth sport. It is argued that some youth athletes participate in highly competitive sport and are encouraged to commit to an athletic career before they have successfully developed the psychosocial skills to manage the challenges associated with competitive sport. Results are discussed with regard to the holistic athletic careers model (Wylleman et al., [2013]. Athletes' careers in Belgium: A holistic perspective to understand and alleviate challenges occurring throughout the athletic and post-athletic career. In N. B. Stambulova, T. V. Ryba, & T. V (Eds.), Athletes' careers across cultures (1st ed, pp. 51–62). Routledge.). There is a need to conduct more research on the early transitions into competitive sport, which may not be developmentally appropriate for young athletes.